Intervenciones de enfermería en pacientes con miomectomía en cirugía robótica: revisión sistemática - Inca Pilco, Katherine Mishel (2026)
Robotic myomectomy is an effective technique for treating uterine fibroids, known for its high precision and fast recovery. However, postoperative nursing intervention guarantees the essential to ensuring optimal recovery and preventing complications, but it lacks a clear systematization. The objective of this study was to identify and systematize the main postoperative nursing interventions in patients undergoing robotic myomectomy, to understand how these interventions influence patient recovery and complication prevention. A systematic literature review was conducted using scientific databases such as PubMed and UpToDate. Studies describing postoperative nursing care for robotic myomectomy were selected. The methodology focused on the analysis of observational, clinical, and retrospective studies. The findings revealed that key interventions such as constant monitoring of vital signs, pain management, early mobilization, infection prevention, and postoperative education are fundamental for successful recovery. Robotic surgery, with its reduced blood loss and shorter operative times, lowers the risk of complications. Emotional support and comprehensive education enhance patient satisfaction and overall well-being. In conclusion, postoperative nursing interventions are essential to optimizing recovery. Proper monitoring, pain management, and complication prevention are crucial. Continuous training of nursing staff is vital to maximize the benefits of robotic surgery